Мифы, легенды и сказки удмуртского народа - Кралина Надежда Петровна (Удмуртия, 2019)
Экземпляры: аб. (20200916) / Инвентарный номер: 60279 / Цена: / Сис.шифр: 82.3(2Рос=Удм)-6 / Авт.знак: М 68 / ГРНТИ: 17.71.91 / ББК: 82.3(2Рос=Удм)-6